Three mitochondrial genomes of Pseudogobio fishes (Cypriniformes: Gobionidae). Issue 3 (2nd July 2020) - Fu, Junwei; Fu, Cuizhang
Abstract: New mitochondrial genomes of Pseudogobio guilinensis, P. giganteus, and P. anderssoni have the length of 16, 605, 16, 606, and 16, 609 bp with A + T bias. Inferred phylogeny shows that P. guilinensis occupies basal position. P. esocinus and P. anderssoni + P. longirostris are sister groups, and they together are a sister taxa of P. giganteus .